The secrets of Vesuvius - Lawrence, Caroline (Lawrence, Caroline. Roman mysteries, 2001)
Ten-year-old Flavia and her friends encounter the Roman admiral Pliny before making a journey to her uncle's farm near Mt. Vesuvius, where they try to solve a riddle, reunite a family, and get out of the path of a natural disaster.